2014
DOI: 10.1002/ejoc.201402232
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Synthesis and Biological Investigations of a Nuphar Alkaloid: Proposed Structure of a Castoreum Component

Abstract: An enantiospecific synthesis of a Nuphar alkaloid was achieved in 9 steps from N-Boc-(L)-proline. The alkaloid is a minor component of castoreum, the dried scent glands of the beaver. During the course of our study, the stereochemistry of three synthetic intermediates was verified by X-ray analysis, which contributes to resolving existing discrepancies among the literature reports regarding the synthesis of this particular compound. Based on our synthesis, we propose the structure of the natural product. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 113 publications
(157 reference statements)
1
7
0
Order By: Relevance
“…), used by the animals to mark their territory ( Maurer and Ohloff, 1976 ). In succession of a chemical study aimed at the elucidation of the stereochemistry of a minor castoreum alkaloid, Seki and Georg (2014) found 5-(3-furyl)-8-methyl-octahydroindolizine ( 2P ) to interact with the oxytocin receptor ( K i = 0.6 μM) suggesting that other nuphar alkaloids might also interact and that similar to the biological roles of oxytocin these alkaloids are used in social communication by beavers. The traditional uses of castoreum including the promotion of menstruation, the expulsion of the placenta and the fetus might well be related to such an interaction ( Matthioli, 1568 , p. 352; Seki and Georg, 2014 ).…”
Section: Review and Discussionmentioning
confidence: 99%
“…), used by the animals to mark their territory ( Maurer and Ohloff, 1976 ). In succession of a chemical study aimed at the elucidation of the stereochemistry of a minor castoreum alkaloid, Seki and Georg (2014) found 5-(3-furyl)-8-methyl-octahydroindolizine ( 2P ) to interact with the oxytocin receptor ( K i = 0.6 μM) suggesting that other nuphar alkaloids might also interact and that similar to the biological roles of oxytocin these alkaloids are used in social communication by beavers. The traditional uses of castoreum including the promotion of menstruation, the expulsion of the placenta and the fetus might well be related to such an interaction ( Matthioli, 1568 , p. 352; Seki and Georg, 2014 ).…”
Section: Review and Discussionmentioning
confidence: 99%
“…The filter cake was washed three times with ethyl acetate and the filtrate was concentrated. The residue was purified via distillation (cold finger,6mm Hg, 30 8C) to give alcohol 8 as ac olourless oil (4.58 g, 46.7 mmol, 65 %); (AE AE)-2-Methylpenta-3,4-dien-1-yl Acetate (9 a) [14] :As olution of the allenic alcohol 8 (2 g, 20.4 mmol) in CH 2 Cl 2 (30 mL) was allowed to stand over molecular sieves (4 ), and then transferred via cannula to af lask containing K 2 CO 3 (4.22 g, 30.6 mmol). Acetic anhydride (2.2 mL, 22.4 mmol) and 4-dimethylaminopyridine (DMAP,1 25 mg, 1.02 mmol) were added.…”
Section: Methodsmentioning
confidence: 99%
“…DMSO (1.48 mL, 1.48 mmol) was added dropwise and the mixture was stirred for 5min. Alcohol 12 (1.89 g, 8.8 mmol) in THF (10 mL) was allowed to stand over molecular sieves (4 ) and then transferred via cannula into the reaction mixture, which was stirred for 15 min. Triethylamine (4.63 mL, 33.2 mmol) was added dropwise and the mixture was stirred for 30 min, then warmed to room temperature.…”
Section: Tert-butyl ((3s4s)-4-methyl-5-oxopent-1-en-3-yl)carbamate (mentioning
confidence: 99%
See 1 more Smart Citation
“…A further set of chain extension transformations were carried out on amino alcohol 1-246 to give key precursor 1-247, N-Boc deprotection with TFA and subsequent NaBH 4 reduction of which, produced piperidine 1-248 in 85% yield as a single diastereomer. The synthesis was completed by heating 1-248 to trigger a second cyclisation and LiAlH 4 reduction of the resulting lactam afforded the target alkaloid 1-239 in 50% yield.Scheme 1.3-27 Bates' synthesis of 1-239Georg and Seki observed that data reported for the structure of 5-(3'furyl)-8methylindolizidine have been inconsistent thus far and a synthetic study was initiated to unequivocally determine the structure of the natural product through an enantiopure synthesis of alkaloids 1-238 and 1-239 (Scheme 1.3-28) 96. The synthesis commenced with reaction of Weinreb amide 1-249 with MeLi, followed by an aldol reaction to introduce the furyl moiety and then oxidation to furnish diketone 1-250.…”
mentioning
confidence: 99%